The extent to which the quality of university education meets the requirements of the quality management system "ISO 9001:2000" An (Applied study in the College of Administration and Economics / Maysan University). - Husham Mayea Fazaa Almusaedi (Peerian Journals Publishing, 2023)
Universities' possession of effective education quality systems is evidence of their scientific achievements and their keenness to provide the best educational services with what the student requires and provide the best outputs (graduates), to meet the labor market, which increased their enthusiasm towards quality education systems that meet the requirements of the present and focus their efforts towards preparing those systems well to reach levels Advanced in the global specifications of quality. This research aims to match the quality of education with the requirements of ISO 9001 in the College of Administration and Economics at the University of Maysan. This research focused on four axes, which are the responsibility of management, resource management, product achievement, measurement, analysis and improvement. With the requirements of ISO 9001, the researchers reached the following conclusions, the most important of which are: The administration shirked its responsibility to improve the reality of the quality of education in the college by following a clear and specific program to raise the level of quality of education.
Keywords: education quality; human resources; responsibility; specializations